D2 lymphadenectomy alone or with No.14v lymph lode dissection for curable distal gastric cancer with clinical stage t4n+m0: a randomized and multicenter phase iii study in China - Liang-Liang Wu; Han Liang (临床与病理杂志, 2026)
Objective: The study is a prospective, open, randomized multicenter phase III clinical trial with two arms that aims to elucidate superiority of D2 plus No.14v lymph node dissection in comparison with standard D2 surgery in patients with curable distal gastric cancer staged cT4N+M0. The primary endpoint is overall survival secondary endpoint is disease-free survival. Each treatment arm includes 255 patients, providing an expected hazard ratio of 0.6. Methods: A prospective, open, randomized multicenter phase III clinical trial was designed to elucidate superiority of D2 plus No.14v lymph node dissection in improving overall survival with regard to standard D2 surgery in patients with curable distal gastric cancer staged cT4N+M0. The study is a multiinstitutional prospective randomized controlled trial, with participating institutions including 20 specialized centers. Treatment methodsEnrolled patients are randomized to 14v- (arm A) or to 14v + (arm B). Results: End points the primary endpoint is overall survival secondary endpoint is disease-free survival. Conclusion: Results are unfinished.